The Relationship between Family Roles and the Success of the Breastfeeding Process at the Neneng Village Health Center in Banjarmasin - Rusmiati Agustina; Reny Retnaningsih (International Journal of Medicine and Health, 2025)
Successful breastfeeding is a crucial factor in ensuring maternal and infant health, yet many postpartum mothers experience obstacles in optimally breastfeeding. One factor that plays a significant role in successful breastfeeding is family support and involvement. Families, particularly husbands and immediate family members, play a strategic role in providing the emotional, informational, and instrumental support mothers need during the postpartum period. This study aims to analyze the relationship between family roles and successful breastfeeding in postpartum mothers at TPMB Bdn. Neneng Banjarmasin. This study employed an observational analytical design with a cross-sectional approach. The sample consisted of 35 postpartum mothers with infants aged 0–6 months selected using purposive sampling. Data were collected using a structured questionnaire to measure family roles and successful breastfeeding, including aspects of early breastfeeding initiation, breastfeeding frequency, maternal comfort, and sustainability of breastfeeding practices. Data were analyzed univariately and bivariately using the Chi-square test with a significance level of p < 0.05. The results showed that most respondents received good family support and that the majority of postpartum mothers experienced successful breastfeeding. Bivariate analysis showed a significant relationship between family roles and breastfeeding success. In conclusion, family roles are significantly associated with breastfeeding success in postpartum mothers. This finding underscores the importance of a family-centered midwifery care approach in supporting breastfeeding success in community midwifery practice.